Edith Penrose's contribution to the resource‐based view of strategic management - Rugman, Alan M.; Verbeke, Alain (Strategic Management Journal, 2002)
Abstract Edith Penrose's (1959) book, The Theory of the Growth of the Firm , is considered by many scholars in the strategy field to be the seminal work that provided the intellectual foundations for the modern, resource‐based theory of the firm. However, the present paper suggests that Penrose's direct or intended contribution to resource‐based thinking has been misinterpreted. Penrose never aimed to provide useful strategy prescriptions for managers to create a sustainable stream of rents; rather, she tried to rigorously describe the processes through which firms grow. In her theory, rents were generally assumed not to occur. If they arose this reflected an inefficient macro‐level outcome of an otherwise efficient micro‐level growth process. Nevertheless, her ideas have undoubtedly stimulated ‘good conversation’ within the strategy field in the spirit of Mahoney and Pandian (1992); their emerging use by some scholars as building blocks in models that show how sustainable competitive advantage and rents can be achieved is undeniable, although such use was never intended by Edith Penrose herself. Copyright © 2002 John Wiley & Sons, Ltd.